CLASSROOM MANAGEMENT AND ARABIC LEARNING PROCESS BASED ON MULTIPLE INTELLIGENCES IN ELEMENTARY SCHOOL - Arifka Mahmudi; Suci Ramadhanti Febriani; Maidatul Hasanah; Zakiyah Arifa (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2019)
This study addressed to explore classroom management and Arabic Learning process based on Multiple intelligences theory implemented by the teacher. The study was a case study with descriptive qualitative approach. The data were collected by interview, documentation, and observation. Then, the data were analyzed with the following steps: data collection, data reduction, data display, verification, and affirmation conclusions. The result of this study revealed that the students were classified based on their intelligences with interview and appropriate test of multiple intelligences done by MIR team. Therefore, Arabic teacher implemented a suitable method in the Arabic learning process for each class based on their needs. Yet, the teacher faced an obstacle when teaching the students with logical-mathematical and interpersonal intelligences. Another data indicated that classroom was not only the class for learning, sometimes the teacher challenged the students to study outdoor, school environment. The school environment and facilities contributed to support learning process and give the students more space to be creative and aware with what they found in the school environment.